2012
DOI: 10.1155/2012/125071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water and Hydrogen Bond Dynamics at the Surface of an Antifreeze Protein

Abstract: We examine dynamics of water molecules and hydrogen bonds at the water-protein interface of the wild-type antifreeze protein from spruce budworm Choristoneura fumiferana and a mutant that is not antifreeze active by all-atom molecular dynamics simulations. Water dynamics in the hydration layer around the protein is analyzed by calculation of velocity autocorrelation functions and their power spectra, and hydrogen bond time correlation functions are calculated for hydrogen bonds between water molecules and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
6
26
0
Order By: Relevance
“…We note that we found a similar trend for another AFP from spruce budworm Choristoneura fumiferana, which also contains a threonine-rich ice-binding plane. In that case, four point mutations, which are found experimentally to dramatically lower antifreeze activity, lead to a similar trend in the hydrogen bond dynamics as we observe here for DAFP-1 (i.e., the hydrogen bond dynamics around all planes are similar for the mutants, whereas they are significantly slower around the icebinding plane for the WT, thereby giving rise to a heterogeneous distribution of the hydration dynamics) (38). Site-specific mutation has a clear nonlocal effect on the entire ice-binding plane.…”
Section: Resultssupporting
confidence: 80%
“…We note that we found a similar trend for another AFP from spruce budworm Choristoneura fumiferana, which also contains a threonine-rich ice-binding plane. In that case, four point mutations, which are found experimentally to dramatically lower antifreeze activity, lead to a similar trend in the hydrogen bond dynamics as we observe here for DAFP-1 (i.e., the hydrogen bond dynamics around all planes are similar for the mutants, whereas they are significantly slower around the icebinding plane for the WT, thereby giving rise to a heterogeneous distribution of the hydration dynamics) (38). Site-specific mutation has a clear nonlocal effect on the entire ice-binding plane.…”
Section: Resultssupporting
confidence: 80%
“…Interestingly, the enhancement of water -water H-bond lifetime upon gradual addition of TMU in aqueous solution resembles the slowing down of water confined in carbon nanotube [105] and water at the surface of an antifreeze protein. [106] Therefore, it may be stated that the presence of TMU slows down the H-bond dynamics in some ways similar to those operative inside the confinement and at the micelle and protein surfaces. One of the frames from the simulation trajectory at X TMU ¼ 0.2 is shown in Figure 9 which depicts the alignment of water and TMU molecules in the binary mixture.…”
Section: Molecular Simulation 477mentioning
confidence: 99%
“…In MD simulation, usually the geometric or the energetic criteria are used to define an HB. Classical atomistic MD simulations have revealed that the relaxation of water−water HB is much faster than that of the protein−water HB . A correlation is established between protein water HB dynamics with the biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Classical atomistic MD simulations have revealed that the relaxation of waterÀ water HB is much faster than that of the proteinÀ water HB. [36,37] A correlation is established between protein water HB dynamics with the biological activity. Thus, important insight can be drawn from studies of solvation dynamics which can shed light on the role of different factors influencing the water dynamics to modulate the behavior of the protein.…”
Section: Introductionmentioning
confidence: 99%